Analisis Prinsip Ḥifẓ Al-Māl Terhadap Pengelolaan Wakaf Corporate: Studi Kasus Kantin UMB Selaku Binaan Sinergi Foundation - Selva Nur Fadhilah; Muhardi; Siska Lis Sulistiani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The development of productive waqf is currently undergoing significant innovation, one of which is managed through the corporate waqf model. In Bandung City, the Sinergi Foundation is among the institutions that manage corporate waqf assets. However, its implementation has not been fully optimal, particularly in the aspect of financial management within the UMB Canteen, which manages corporate waqf funds. This study aims to analyze the application of the Islamic principle of hifdzu al-maal in the management of productive waqf by the Sinergi Foundation in Bandung City, with a case study on the waqf fund management through the canteen unit at Universitas Muhammadiyah Bandung (UMB) as one of its fostered SMEs. A qualitative approach was employed in this study, utilizing data collection techniques such as observation, interviews, and documentation. The findings reveal that, in general, the management of corporate waqf at the Sinergi Foundation has reflected the principle of hifdzu al-maal (safeguarding assets) as taught in the maqashid sharia. Specifically, the management of the UMB Canteen corporate waqf has fulfilled one of the four principles of hifdzu al-maal, namely ensuring productive endowments sourced from lawful assets. Meanwhile, other aspects—such as responsible asset utilization, asset protection and security, and asset development—still require improvement. These improvements may be achieved through the implementation of an accountable bookkeeping system, stricter cash flow management, financial management training for canteen managers, periodic monitoring and evaluation, as well as enhanced transparency and accountability.